NeuroSAFE robot-assisted laparoscopic prostatectomy versus standard robot-assisted laparoscopic prostatectomy for men with localised prostate cancer (NeuroSAFE PROOF): protocol for a randomised controlled feasibility study. Issue 6 (11th June 2019) - Dinneen, Eoin; Haider, Aiman; Allen, Clare; Freeman, Alex; Briggs, Tim; Nathan, Senthil; Brew-Graves, Chris; Grierson, Jack; Williams, Norman R; Persad, Raj; Oakley, Neil; Adshead, Jim M; et al.
Abstract : Introduction: Robot-assisted laparoscopic prostatectomy (RALP) offers potential cure for localised prostate cancer but is associated with considerable toxicity. Potency and urinary continence are improved when the neurovascular bundles (NVBs) are spared during a nerve spare (NS) RALP. There is reluctance, however, to perform NS RALP when there are concerns that the cancer extends beyond the capsule of the prostate into the NVB, as NS RALP in this instance increases the risk of a positive surgical margin (PSM). The NeuroSAFE technique involves intraoperative fresh-frozen section analysis of the posterolateral aspect of the prostate margin to assess whether cancer extends beyond the capsule. There is evidence from large observational studies that functional outcomes can be improved and PSM rates reduced when the NeuroSAFE technique is used during RALP. To date, however, there has been no randomised controlled trial (RCT) to substantiate this finding. The NeuroSAFE PROOF feasibility study is designed to assess whether it is feasible to randomise men to NeuroSAFE RALP versus a control arm of 'standard of practice' RALP. Methods: NeuroSAFE PROOF feasibility study will be a multicentre, single-blinded RCT with patients randomised 1:1 to either NeuroSAFE RALP (intervention) or standard RALP (control). Treatment allocation will occur after trial entry and consent. The primary outcome will be assessed as the successful accrual of 50 men at three sites over 15 months. Secondary outcomes will be used to aid subsequent power calculations for the definitive full-scale RCT and will include rates of NS; PSM; biochemical recurrence; adjuvant treatments; and patient-reported functional outcomes on potency, continence and quality of life. Ethics and dissemination: NeuroSAFE PROOF has ethical approval (Regional Ethics Committee reference 17/LO/1978). NeuroSAFE PROOF is supported by National Institute for Healthcare Research Research for Patient Benefit funding (NIHR reference PB-PG-1216-20013). Findings will be made available through peer-reviewed publications. Trial registration number: NCT03317990 .